Hubungan Antara Kelelahan dan Sindrom Burnout Pada Residen di Departemen Anestesiologi dan Terapi Intensif - Venawati, Feni; Lubis, Andriamuri Prima; Bangun, Chrismas Gideon; Yunanda, Yuki (Jurnal Biomedika dan Kesehatan, 2023)
Background Anesthesiologists in Indonesia are still in high demand. The large number of patients and the heavy workload faced by residents are accompanied by quite high pressure from various aspects, this can cause anesthesia resident participants to experience fatigue so they are prone to a syndrome called burnout syndrome. This study aims to determine the relationship between fatigue and burnout syndrome among residents in the Anesthesiology and Intensive Therapy Department, Faculty of Medicine, Universitas Sumatera Utara. Methods This study was a cross-sectional study on 106 residents that was performed using a questionnaire consisting of characteristics of study samples, translated Fatigue Assessment Scale (FAS), and Maslach Burnout Inventory-Human Service Survey (MBI-HSS). Results From the analysis, it was discovered that 50% of the residents didn’t experience fatigue with a median score of FAS 21.5, and 84.9% of the residents didn’t experience burnout syndrome with a median score of MBI-HSS was 51,84 ± 19,59. There was a significant relationship between FAS and total score of MBI-HSS, emotional exhaustion, depersonalization, and personal achievement with p-value <0.001. Conclusions There was a significant relationship between FAS and total score of MBI-HSS, emotional exhaustion, depersonalization, and personal achievement.